Analisis dan Evaluasi File Storage and Backup di Diskominfo Data Center - Endang Amalia Furkon (Jurusan Informatika Universitas Jenderal Achmad Yani, 2020)
Disaster is a very damaging and unpredictable event when it happens, threatening the facilities of computer systems and the environment, such as telecommunications systems and data storage. According to the National Disaster Management Agency (BNPB) Indonesia is very vulnerable to disasters because of the geographical characteristics. Indonesia current position is between three active plates and a ring of fire. Indonesia's reputation as a disaster-prone country is also noted in the report of The Atlas of the Human Planet 2017. The data shows that the threat of natural disasters has doubled in the last 40 years, in line with the population growth. Diskominfo West Java is an agency that is tasked with carrying out regional government affairs in West Java in the field of communication and information technology based on the principles of autonomy, deconcentration and co-administration. Diskomifo has a data center that is useful for the benefit of the information itself and the Regional Work Unit (SKPD) of the West Java provincial government. A data center must be designed as best as possible to avoid disruption due to disasters, disturbances or errors that can cause damage to the data center itself, therefore it must be avoided or minimized from the impact of the risks that occur and guarantee the availability of the organization's business continuity if interference or disaster is occurred. In this study, an analysis was carried out related to the assessment of risk occurrence, to determine the level of the threats. In addition, in this document a business impact analysis is also carried out to determine the priorities of the information system owned by the organization, so that the organization can prioritize which information system is in the top priority when disruptions occured.